Early sensory re-education of the hand after peripheral nerve repair based on mirror therapy: a randomized controlled trial - Paula,Mayara H. (2016)
BACKGROUND: Mirror therapy has been used as an alternative stimulus to feed the somatosensory cortex in an attempt to preserve hand cortical representation with better functional results. OBJECTIVE: To analyze the short-term functional outcome of an early re-education program using mirror therapy compared to a late classic sensory program for hand nerve repair. METHOD: This is a randomized controlled trial. We assessed 20 patients with median and ulnar nerve and flexor tendon repair using the Rosen Score combined with the DASH questionnaire. The early phase group using mirror therapy began on the first postoperative week and lasted 5 months. The control group received classic sensory re-education when the protective sensation threshold was restored. All participants received a patient education booklet and were submitted to the modified Duran protocol for flexor tendon repair. The assessments were performed by the same investigator blinded to the allocated treatment. Mann-Whitney Test and Effect Size using Cohen's d score were used for inter-group comparisons at 3 and 6 months after intervention. RESULTS: The primary outcome (Rosen score) values for the Mirror Therapy group and classic therapy control group after 3 and 6 months were 1.68 (SD=0.5); 1.96 (SD=0.56) and 1.65 (SD=0.52); 1.51 (SD=0.62), respectively. No between-group differences were observed. CONCLUSION: Although some clinical improvement was observed, mirror therapy was not shown to be more effective than late sensory re-education in an intermediate phase of nerve repair in the hand. Replication is needed to confirm these findings.